COASTAL WATER QUALITY AT VUNG TAU MONITORING STATION (1997 - 2014) - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2016)
Analysis results of coastal water samples in Vung Tau monitoring station from 1997 to 2014 showed that the values of the basic parameters (salinity: 20.9 - 34.2‰, pH: 7.73 to 8.53, total suspended solids: 2.4 - 627 mg/l; DO: 4.76 - 7.64 mg/l), BOD5: 0.30 - 2.66 mg/l, nutrients (ammonium: 0 - 322 μgN/l; nitrite: 1.5 - 148.1 μgN/l; nitrate: 60 - 719 μgN/l; phosphate: 1.0 - 30 μgP/l; silicate: 191 - 3,975 μgSi/l); organic matters (N: 420 - 1,265 μg/l; P: 41 - 741 μg/l), heavy metals (Zn: 7.1 - 59.4 μg/l; Cu: 0.5 - 10.8 μg/l; Pb: 0.2 - 4.6 μg/l; As:1.0 - 6.4 μg/l; Cd: 0 - 2.7 μg/l; Hg: 0 - 0.81 μg/l ), hydrocarbons (79 - 925 μg/l) and coliform density (0 - 19,300 MPN/100 ml) changed widely. However, the values of the surveyed parameters were often in the limited values of criteria on coastal water quality for aquatic life protection. Difference of water quality parameters over the season, tide and layer was only clear for salinity and silicate. The analysis of environmental data during the last two decades showed that there were the decreasing trend of DO in rainy season and the increasing trend of phosphate, organic P, Pb and HC in both seasons. This was a sign of declining seawater quality in monitoring station.